Properties of the TiO2 membranes prepared by CVD of titanium tetraisopropoxide - Ha, HY; Nam, SW; Lim, TH; Oh, IH; Hong, SA (ELSEVIER SCIENCE BV, 1996)
Thin films of TiO2 were deposited on the inner surface of porous Vycor glass tubes by atmospheric pressure chemical vapor deposition (APCVD) at temperatures ranging from 200 to 400 degrees C using titanium isopropoxide as a precursor. Dense and hydrogen-permselective membranes were formed only in the temperature range between 230 and 300 degrees C. Gas permeation through the dense membrane was governed by an activated diffusion mechanism and the H-2:N-2 permeation ratio was far beyond the range of Knudsen diffusion. At 200 and 400 degrees C, however, highly porous films were formed and the permselectivity of the membrane was not improved at all, because gas permeation through the porous membrane was in the Knudsen diffusion regime. Selectivity (H-2:N-2 permeation ratio) profile showed a maximum value of 57 at a deposition temperature of 250 degrees C. The oxygen added to the reaction environment appeared to have some effects on the stability and the permselectivity of the membrane formed. The permeation properties of the TiO2 membranes were not so appreciable and the stability of the membrane was poor when compared with dense SiO2 membranes. The characterization of the TiO2 films by SEM and TEM reveals that phase change from amorphous to crystalline state occurs at a temperature about 300 degrees C.
Keywords: CHEMICAL-VAPOR-DEPOSITION; CERAMIC MEMBRANE; FILMS; TEMPERATURE